Factors Associated With Deep Sedation Practice in Mechanically Ventilated Patients: A Post hoc Analysis of a Cross–Sectional Survey Combined With a Questionnaire for Physicians on Sedation Practices - Ma, Penglin; Wang, Tao; Gong, Yichun; Liu, Jingtao; Shi, Wei; Zeng, Lin (Frontiers in Medicine, 2022)
Purpose The study aimed to explore factors associated with deep sedation practice in intensive care units (ICUs). Materials and Methods A post hoc analysis was conducted for a cross–sectional survey on sedation practices in mechanically ventilated (MV) patients, combined with a questionnaire for physicians regarding their preferences for light sedation (P–pls Score) in 92 Chinese ICUs. Results There were 457 and 127 eligible MV patients in the light and deep sedation groups respectively. A multivariable logistic regression analysis demonstrated that the control mode of mechanical ventilation, plasma lactate level, and the Sequential Organ Failure Assessment (SOFA) score were independent risk factors for deep sedation practice (p <0.01). Notably, the adjusted odds ratio (95% CI) of the average P–pls score in the ICU ≤ 2 for deep sedation practice was 1.861 (1.163, 2.978, p = 0.01). In addition, the areas under curves of receiver operating characteristics (AUC–ROC) of the model to predict the probability of deep sedation practice were 0.753 (0.699, 0.806) and 0.772 (0.64, 0.905) in the training set and the validation set, respectively. The 28–day mortality was increased in patients with exposure to deep sedation practice but not significantly. Conclusion Both factors related to stressful stimuli and the ICU physicians' perception of patient tolerability in mechanical ventilation were likely associated with deep sedation practice in MV patients.